Analysing the potential of retrofitting ultra-low heat loss triple vacuum glazed windows to an existing UK solid wall dwelling - Memon, Saim (International Journal of Renewable Energy Development, 2014)
Heat loss through the windows of solid wall dwellings is one of the factors contributing to high energy consumption for space heating ensuing in preventable carbon emissions. This research forms a part of novel contribution in vacuum glazing science presenting the refurbishment technology of an experimentally achievable thermal performance of triple vacuum glazing to existing UK solid wall dwelling by investigating the space-heating load, solar energy gain and window to wall area ratios. Three-dimensional dynamic thermal models, considering realistic heating and occupancy regimes, of an externally insulated solid wall dwelling with single glazed, double glazed air filled, double glazed argon gas filled, triple glazed air filled and triple vacuum glazed windows were developed. Predictions for the simulated dwelling when replacing single glazed windows with triple vacuum glazed windows indicate space-heating energy saving of 14.58% (871.1 kWh) for the winter months (Dec, Jan and Feb); predicted annual energy savings are 15.31% (1863.5 kWh). The predicted reduction in the solar energy gains for the triple vacuum glazing was 75.3 kWh in the winter months. The effects on solar energy gain are analysed and the potential to increase window-to-wall area ratios (WWR’s) examined. For a simulated room with triple vacuum glazed windows increasing the WWR’s from 5% to 59% led to a reduction in the predicted required space-heating; whilst for a room with single glazed, double air filled, double argon gas filled and triple air filled windows the predicted required space-heating increased with increasing WWR. It was shown that retrofitting existing solid wall dwelling with triple vacuum glazed windows could be a robust retrofit solution in improving building energy efficiency. This research also implicates a need of the cost-effective development of triple vacuum glazing at the manufacturing level, which would then be more beneficial to consumers in terms of energy and cost savings.